Retention of metals in periprosthetic tissues of patients with metal-on-metal total hip arthroplasty is reflected in the synovial fluid to blood cobalt transfer ratio in the presence of a pseudotumour - Tomi Nousiainen (BMC Musculoskeletal Disorders, 2020)
Abstract Background Modern metal-on-metal (MOM) arthroplasties were performed for over a decade before alarming reports of adverse metal reactions dramatically reduced their use. Failures are seen more often with high-wearing implants, but also well-positioned components with more favourable wear patterns can cause problems. There are no specific clinical indicators that could help us to predict the prognosis of these implants. For this reason, we still need more information on the effect of underlying factors that contribute to this process. Methods In this prospective cohort study, we investigated how cup orientation and type of pseudotumour determined by the Hart classification effect the distribution of metals in blood, synovial fluid and tissues surrounding the metal-on-metal hip prosthesis in revision surgery patients. One thousand two hundred twenty-nine metal-on-metal hip patients were screened and of those, 60 patients that had a revision surgery due to adverse metal reaction were included. Whole blood, synovial fluid and synovial/pseudotumour tissue samples were analysed for metal ion concentrations (Co, Cr, Mo and Ti). Results The lowest metal concentrations were found when both cup anteversion and inclination were optimal, and the highest when both were suboptimal. Suboptimal anteversion alone raised Cr-ion concentrations more than suboptimal inclination. The concentrations of metals in blood, synovial fluid or synovial soft tissue were the same in patients with and without a pseudotumour, but the relative transfer percentage of cobalt from synovial fluid to blood was higher in patients with a pseudotumour. Conclusions The implant orientation alone does not explain the metal concentrations found in tissues or distribution of metals between different tissues. The accumulation of metals in periprosthetic soft tissues increase the total metal load, and in the presence of a pseudotumour this is reflected in the transfer ratio of Co from synovial fluid to the blood. The total metal load of the pseudotumour tissue should be defined in future studies to determine if this will provide new insights for clinical practice.